Development and validation of the adolescents’ perceptions of parental involvement scale in China - Liu, Xuerong; Gong, Zheng; Li, Wei; Lei, Jingyu; Han, Xiaodi; Wang, Yaozhi; Wang, Xueqian; Shi, Liping; Zhang, Qiongzhi; Zhang, Qianyu; Zhang, Heng; Li, Zhanghong; et al. (Frontiers in Psychology, 2025)
IntroductionGiven the increasing academic pressures associated with intensified social competition, the role of parental involvement in education has emerged as a pivotal research area, especially within the context of Chinese culture. However, there remains a need to further delineate the characteristic dimensions of parental involvement and to develop appropriate measurement tools to quantify such involvements. By the perspective from adolescents’ reports, this study proposed a psychometric and theoretical framework for understanding Chinese adolescents’ perceptions to their parental involvement.MethodsWe adopted a mixed-methods approach across three studies. In Study 1, we conducted structural interviews with adolescents aged 12 to 18, applying grounded theory to analyze their perceptions of parental involvement. Study 2 involved the creation and refinement of a measurement questionnaire through exploratory factor analysis. Study 3 validated these dimensions through confirmatory factor analysis and criterion-related validity tests on national samples.ResultsStudy 1 identified four preliminary characteristic dimensions of perceived parental involvement: emotional involvement, academic involvement, life involvement, and social involvement. In Study 2, we developed a four-dimensional 21-item questionnaire showing high conceptional validity. Study 3 demonstrated strong reliability and construct validity for this questionnaire across different samples.DiscussionThis research provides a new understanding of the characteristic dimensions of adolescents’ perceptions of parental involvement and introduces an effective measurement tool.